2018
DOI: 10.1103/physrevd.98.024018
|View full text |Cite
|
Sign up to set email alerts
|

Rotating accretion flows in D dimensions: Sonic points, critical points, and photon spheres

Abstract: We give the formulation and the general analysis of the rotational accretion problem on Ddimensional spherical spacetime and investigate sonic points and critical points. First, we construct the simple two-dimensional rotating accretion flow model in general D-dimensional static spherically symmetric spacetime and formulate the problem. The flow forms a two-dimensional disk lying on the equatorial plane and the disk is assumed to be geometrically thin and has uniform distribution in the polar angle directions.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…We can easily observe that SP/PS correspondence holds in Schwarzschild (anti) de-Sitter spacetime from the work by Mach et al [7] with the knowledge that the spacetime has a photon sphere on the radius 3M . Surprisingly, it was recently found that SP/PS correspondence always holds in arbitrary static spherically symmetric spacetime of arbitrary dimensions for spherical flow [9] and rotational flow [10]. In addition to its applications to observations in astrophysics, SP/PS correspondence has interesting implications concerning fundamental mechanism of fluid dynamics on curved spacetime.…”
mentioning
confidence: 99%
“…We can easily observe that SP/PS correspondence holds in Schwarzschild (anti) de-Sitter spacetime from the work by Mach et al [7] with the knowledge that the spacetime has a photon sphere on the radius 3M . Surprisingly, it was recently found that SP/PS correspondence always holds in arbitrary static spherically symmetric spacetime of arbitrary dimensions for spherical flow [9] and rotational flow [10]. In addition to its applications to observations in astrophysics, SP/PS correspondence has interesting implications concerning fundamental mechanism of fluid dynamics on curved spacetime.…”
mentioning
confidence: 99%
“…Recently, it was shown that there is a correspondence between the sonic points of ideal photon gas and the photon sphere in static spherically symmetric spacetimes [44]. This important result is valid not only for spherical accretion of the ideal photon gas, but also for rotating accretion in static spherically symmetric spacetimes [45][46][47]. In this section, we establish this correspondence in the parameterized spherically symmetric black hole.…”
Section: Correspondence Between Sonic Points Of Photon Gas and Photon...mentioning
confidence: 57%
“…Recently, it was shown that there is a correspondence between the sonic points of accreting ideal photon gas and the photon sphere in static spherically symmetric spacetimes [44]. This important result is valid not only for spherical accretion of the idea photon gas, but also for rotating accretion in static spherically symmetric spacetimes [46,47]. In an observational viewpoint, as mentioned in [47], this correspondence connects two independent observations, the observation of lights from sources behind a black hole and the observation of emission from accreted radiation fluid onto the black hole, because the size of the shadow of the hole is determined by the radius of the photon sphere and the accreted fluid can signal the sonic point.…”
Section: Introductionmentioning
confidence: 89%
“…Static, spherically symmetric spacetimes, which describe strong gravitational fields caused by compact objects, have circular photon orbits and the set of the photon orbits is called photon (antiphoton) sphere if it is unstable (stable) [4]. The property of the (anti)photon sphere such as the upper bound of the radius [5] and number [6] has been investigated since the (anti)photon sphere is related in phenomena in the strong gravitational field such as the high-frequency behavior of the photon absorption cross section [7,8], stability of thinshell wormholes [9,10], the high-frequency spectrum of quasinormal modes of compact objects [11][12][13], a centrifugal force and gyroscopic precession [14][15][16][17], Bondi's sonic horizon of a radial fluid [18][19][20][21][22][23], and an apparent shape during a collapsing star to be a black hole [24][25][26]. Extensions and alternatives of the photon sphere have been investigated [27][28][29][30][31][32][33][34][35][36][37][38][39] and instability of the compact objects caused by the slow decay of linear waves near stable photon rings has been considered [40][41][42].…”
Section: Introductionmentioning
confidence: 99%